ANALISIS PENGARUH KUALITAS PRODUK , KUALITAS PELAYANAN, KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA PT NUSANTARA SURYA SAKTI) - Rachmawaty Haroen (Jurnal Manajemen dan Bisnis Jayakarta, 2020)
Hypothesis test by using partial correlation coefficient analysis showed that correlation coefficient (r) variable of product quality = 0,197 mean relationship of product quality variable with customer loyalty variable is categorized very weak, correlation coefficient value (r) service quality variable = 0,365 mean relationship of service quality variable With customer loyalty variable is categorized as weak, correlation coefficient value (r) customer trust variable = 0,347 mean relationship of customer's trust variable with customer loyalty variable is categorized weak. While simultaneously the result of simultaneous correlation coefficient analysis based on the result of processing SPSS 20 is the value of simultaneous correlation coefficient (R) = 0.387. Value 0.387 is in the range 0.40-0.60, means the relationship of product quality variables, service quality, and customer confidence simultaneously with customer loyalty variables categorized quite good or significant enough. This is proved by the value of determination coefficient KD = (R2 x 100%) = 0,3872 x 100% = 14,97%, mean equal to 14,97% as contribution of variable value of product quality, service quality, customer trust to customer loyalty. While the rest of 85.03% is the contribution of other variables that are not examined. The conclusion of the research is, Product Quality, Service Quality, and Customer Confidence together influential on Customer Loyalty.